Absence of intestinal inflammation and postoperative ileus in a mouse model of laparoscopic surgery. Issue 9 (26th June 2014) - Gomez‐Pinilla, Pedro J.; Binda, Maria M; Lissens, Ann; Di Giovangiulio, Martina; van Bree, Sjoerd H.; Nemethova, Andrea; Stakenborg, Nathalie; Farro, Giovanna; Bosmans, Goele; Matteoli, Gianluca; Deprest, Jan; Boeckxstaens, Guy E
Abstract Background Postoperative ileus (POI) is characterized by impaired gastrointestinal motility resulting from intestinal handling‐associated inflammation. The introduction of laparoscopic surgery has dramatically reduced the duration of POI. However, it remains unclear to what extent this results in a reduction of intestinal inflammation. The aim of the present study is to compare the degree of intestinal inflammation and gastrointestinal transit following laparoscopic surgery and open abdominal surgery. Methods Mice were subjected to laparoscopic surgery or laparotomy alone or, in combination with standardized intestinal manipulation of the small bowel (IM). Gastrointestinal transit and intestinal inflammation were assessed 24 h after surgery by the number of myeloperoxidase (MPO) positive cells and the level of cytokine expression. The recovery time and the degree of inflammation were also analyzed in patients subjected to colectomy under open conditions (laparotomy) or laparoscopic conditions. Key Results Mice undergoing IM by laparotomy (open IM), but not by laparoscopy (Lap IM) developed a significant delay in gastrointestinal transit compared to laparotomy or laparoscopy alone. In addition, there was significant intestinal inflammation only after open IM. Similarly, cytokine levels in peritoneal lavage fluid were lower while recovery time was faster in patients subjected to colectomy under laparoscopic conditions compared to open colectomy. Conclusions & Inferences Our data confirms that intestinal inflammation is underlying the delayed gastrointestinal transit observed after open surgery. Most importantly, we demonstrate that intestinal inflammation under laparoscopic conditions is significantly lower compared to open surgery, most likely explaining the faster recovery following laparoscopic surgery.